ITIKAD BAIK PENGUASAAN FISIK SEBAGAI DASAR PEROLEHAN KEPEMILIKAN HAK ATAS TANAH (ANALISIS PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 269PK/PDT/2015) - EPIPANNI SIHOTANG (PREMISE LAW JURNAL, 2017)
Legal consequence land transact with good faith which is made fraudulent causes the land transfer to be illegal, to have no legal certainty, and to have no legal protection. The Judges’ decision in the Supreme Court’s Ruling No. 269PK/PDT/2015 is not accurate since the plaintiff as the buyer is considered negligent to see who is the real owner of the land and the object of the transact; He is considered having no good faith since he buys it even though he knows that it is occupied, and the plaintiff cannot give evidence of the validity in land transfer consecutively up to the right holder until the registration according to Article 24, paragraph 1. The judges’ consideration in the Supreme Court’s Ruling No. 269PK/PDT/2015 is not accurate because it is not in accordance with legal facts and does give concrete reasons, basic decision, and certain Articles of legal Provisions or unwritten legal source in pronouncing judgment.Keywords: Buyer with Good Faith, Land Right Transfer